Новый индекс демократии. Демократизация общественности в пятнадцати государствах Европы (1991–1998) - Херпфер, К. (Социология: теория, методы, маркетинг, 2001)
The author suggests a new index of democracy developed as a result of analysis of new democracies in post-communist countries. The index can be applied in order to measure society democratization degrees while non-democratic regimes transform into democratic ones at the individual level of social environment: from rising and consolidate democracies to mature ones. The index is constructed on the 9-item base and makes it possible to determine correlation between a democratic support degree and personal indicators, like educational level, place of residence, age and gender.